Produktivitas Air Beberapa Varietas Selada dengan Sistem Irigasi NFT (Nutrient Film Technique) di PT. Momenta Agrikultura Lembang Bandung Barat - Widya Sari; Muhammad Idrus; Surya Surya (Jurusan Teknologi Pertanian, 2015)
The research was conducted at the PT. Momenta Agrikultura Lembang West Bandung on February to April 2015. The objectives of the research were to determine amount of water used, production, and water productivity on several varieties of salad (Lactuca sativa L.) with irrigation system nutrient film technique (NFT). The result of the research showed that the variety of salad affected amount of water used, production and water productivity of salad with irrigation system nutrient film technique (NFT). The amount of water used of several salad varieties were 23.52 l/plant of cyurly salad, 25.02 l/plant of red salad, 12.71 l/plant of romain salad, and 15.09 l/plant of batavia salad for one circle of planting 45 days. Production of batavia salad were 170.2 g/plant not significantly different compared to romain salad of 166.0 g/plant but higher compared to curly salad of 142.6 g/plant and red salad of 94.2 g/plant. Water productivity of romain salad were 13.60 kg/m3 not significantly different compared to batavia salad of 11.91 kg/m3 but higher compared to curly salad of 6.18 kg/m3 and red salad of 3.77 kg/m3. Keywords: salad varieties (curly salad, red salad, romain salad, and batavia salad), irrigation system nutrient film technique (NFT), water used, production, and water productivity